The coexistence of concha bullosa and nasal septum deviation in adult Nigerians - Beryl Shitandi Ominde; Patrick Sunday Igbigbi (Indian Journal of Health Sciences and Biomedical Research KLEU, 2022)
BACKGROUND: Concha bullosa (CB) with an associated nasal septum deviation (NSD) compromises the paranasal sinus drainage through the osteomeatal complex hence predisposing to sinus disease. This study aimed at elucidating the concomitant existence of CB and NSD in adult Nigerians. MATERIALS AND METHODS: Following institutional ethical approval, brain computed tomography images of 336 patients (199 males and 137 females) aged ≥ 20 years were analyzed for CB and NSD in the Radiology Department of a Teaching Hospital. Using the Statistical Package for the Social Sciences software version 23, the prevalence of these variants was expressed in percentages, and their association was probed using the Chi-square test. The angle of septum deviation was summarized in means and standard deviations. The differences in deviation angle in the presence of either ipsilateral or contralateral CB were assessed using the independent t-test. P < 0.05 was considered statistically significant. RESULTS: The prevalence of coexisting CB and NSD was 77, 22.9%. There was a significant preponderance of NSD away from a unilateral or dominant CB (54, 84.4%) (P = 0.022). This deviation occurred at a significantly higher angle (11.82° ± 2.21°) than deviation toward a CB (9.86° ± 2.63°) (P = 0.036). CONCLUSION: The awareness of the association between CB and NSD in our population emphasizes on mandatory preoperative radiological evaluation to aid in planning for safe endoscopic surgeries through the nose.